Social inequalities in overweight and obesity in 26 European countries. (30th September 2020) - Charafeddine, R; Demarest, S; Drieskens, S; Renard, F
Abstract: Background: Previous studies have shown inequalities in overweight and obesity in disfavor of the socially disadvantaged groups. This study examines the extent of these inequalities in 26 European countries. Methods: Data from the 2017 EU Statistics on Income and living Conditions (EU-SILC) were used (18 years and older, n = 482, 595). A body mass index of 25.0 to 29.9 kg/m2 was classified as overweight and 30.0 and more as obese. Educational level (EL) was used as socioeconomic indicator. Generalized linear models were fitted to compute low-versus high absolute (RD) and relative (RR) inequality. Absolute inequality amplitude (RDA) was calculated as RD/Prevalence. Results: Among men, average EU inequalities for overweight were slightly in disfavor of the low educated (RR = 1.05, RDA=5%). A mixed inequality pattern was observed across countries, as the risk of overweight was higher among high educated men in most Eastern countries, in contrast to other parts of Europe (RR from 0.74 to 1.19, RDA from -27% to 20%). Male obesity showed more pronounced inequalities (RR = 1.22, RDA=18%), and a consistent pattern of higher risk among the low educated and wide variation across countries (RR from 1.20 to 2.18, RDA from 16% to 49%). Among women, significant inequalities in overweight were observed (RR = 1.23, RDA=21%), with a consistent pattern of higher risk among the lowest EL, and substantial variation across countries (RR from 1.06 to 1.53, RDA from 7% to 36%). Inequalities were even larger for female obesity, with average RR and RDA reaching 1.49 and 35%, and wider variation (RR from 1.35 to 2.77, RDA from 12% to 88%). Conclusions: Social inequalities in weight status are widespread in Europe, but vary substantially between countries. Inequalities are larger among women. For male overweight, a reverse inequality is observed in most Eastern countries. This study allows countries to benchmark the inequalities observed nationally to the situation in other EU countries. Key messages: Social inequalities in weight status are widespread in Europe. The pattern of social inequalities in overweight and obesity varies substantially by country and gender.